Misi dan Diakonia dalam Gereja - Eleven, Sihotang (JURNAL DIAKONIA, 2021)
Mission and diakonia are two things but unity which is integrated within a church body. A church not as a church if it doesn’t do mission and diakonia. Diakonia is a mission in action. To do diakonia it means to be ready to witness about God’s love. The existence of the church is to proclaim the Good News to the poor; to heal the sick and brokenhearted; freedom to the prisoners and recovery of sight for the blind, to set the oppressed free and to create serenity to the people in hardship, injustice, and the victim of violence, sex abuse and other difficult circumstances. Proclaiming of the church through diakonia services by using hands, feet, eyes, noses, mouths, ears, heart and all part of the church body. Preach the Gospel it’s not only from the pulpit but go in to amid of people in need and do diakonia services.